1.9 THz selective injection design quantum cascade laser operating at extreme higher temperature above the kBT line. Issue 11 (25th September 2013) - Miho, Sasaki; Lin, Tsung‐Tse; Hirayama, Hideki; Yamaguchi, Hiroshi; Kumakura, Kazuhide
Abstract The terahertz quantum cascade laser (THz‐QCL) is a promising compact THz laser source with high output power and narrow emission line width, and could be put to use in a variety of applications. However, the operating temperature of lower frequency (< 2 THz) QCLs is particularly low, and is limited by the kBT line. This paper demonstrates a 1.9 THz GaAs/Al0.175Ga0.825As QCL operating at temperatures much higher than the kBT line. A selective injection scheme (using a four‐level design) with high‐Al composition barrier was used to build the low‐frequency QCL with high operating temperature. We succeeded in surpassing the kBT line limit for a 1.9 THz QCL that operates up to 160 K (∼1.8 ħw/kB). The selective injection 1.9 THz QCL shows one‐frequency lasing operation over the entire injection bias voltage range. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)